Erratum on the article ‘A feasibility study of using composite reinforcement in transport and power industry structures’ (doi:10.3846/16484142.2017.1342689) - Vanagas, Egidijus; Kliukas, Romualdas; Lukoševičienė, Ona; Maruschak, Pavlo; Patapavičius, Andrius; Juozapaitis, Algirdas (Transport, 2017)
"Erratum on the article ‘A feasibility study of using composite reinforcement in transport and power industry structures’ (doi:10.3846/16484142.2017.1342689)." Transport, 32(4), p. 435